2020
DOI: 10.1002/prp2.579
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, mass balance, tissue distribution, metabolism, and excretion of praliciguat, a clinical‐stage soluble guanylate cyclase stimulator in rats

Abstract: The pharmacokinetics (PK), metabolism, excretion, mass balance, and tissue distribution of [14C]praliciguat were evaluated following oral administration of a 3‐mg/kg dose in Sprague‐Dawley rats and in a quantitative whole‐body autoradiography (QWBA) study conducted in male Long‐Evans rats. Plasma Tmax was 1 hour and the t1/2 of total plasma radioactivity was 23.7 hours. Unchanged praliciguat accounted for 87.4%, and a minor metabolite (N‐dealkylated‐praliciguat) accounted for 7.6% of the total radioactivity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Pharmacokinetic data from prior clinical trials showed that praliciguat has a high apparent volume of distribution, suggesting extensive distribution to extravascular tissues (36,37). Furthermore, in rodent studies, oral administration of praliciguat led to high tissue-plasma ratios in several organs, including the kidney (cortex and medulla), heart, liver, and adipose tissue (32). Kidney clearance of praliciguat is negligible in humans, suggesting it could potentially be used without dose adjustment in patients with reduced kidney function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic data from prior clinical trials showed that praliciguat has a high apparent volume of distribution, suggesting extensive distribution to extravascular tissues (36,37). Furthermore, in rodent studies, oral administration of praliciguat led to high tissue-plasma ratios in several organs, including the kidney (cortex and medulla), heart, liver, and adipose tissue (32). Kidney clearance of praliciguat is negligible in humans, suggesting it could potentially be used without dose adjustment in patients with reduced kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Praliciguat (IW-1973) is an orally available sGC stimulator characterized by extensive distribution to tissues, including the kidney medulla and cortex (23,31,32). Praliciguat inhibited proinflammatory and profibrotic responses in isolated human kidney proximal tubular cells (33) and ameliorated proteinuria and kidney damage in animal models of nephropathy, including at doses that had minimal effects on systemic BP in multiple rat models (34,35).…”
Section: Introductionmentioning
confidence: 99%
“…At week 13 , hypertensive rats with HFD were randomly assigned to four different groups: without any treatment (vehicle group; n = 15); treated with a sodium-glucose cotransporter 2 inhibitor (EMPA, 7 mg/kg/day) in drinking water (EMPA group; n = 8); treated with an sGC stimulator (PRL, 10 mg/kg/day) formulated in the HFD (Research Diets, D18071902) (PRL group; n = 10); or treated with EMPA and PRL as aforementioned (EMPA + PRL group, n = 10). PRL is a highly selective sGC stimulator with rapid absorption, high bioavailability, and nonrenal clearance ( 20 , 21 ) that improves cardiorenal damage by reducing AP and several markers of inflammation and fibrosis ( 22 ). The sGC stimulator, PRL binds to and stimulates heme-containing NO-responsive sGC.…”
Section: Methodsmentioning
confidence: 99%
“…The nitric oxide (NO)-soluble guanylate cyclase (sGC)-3′,5′cyclic guanosine monophosphate (cGMP) signaling pathway is increasingly recognized as a potential therapeutic target for human diseases with a metabolic component (Buys et al, 2018). Praliciguat (IW-1973, PRL) is a small-molecule sGC stimulator that potentiates the NO-cGMP pathway (Banijamali et al, 2020;Hanrahan et al, 2020a;Liu et al, 2020;Shea et al, 2020); thereby increasing cGMP production leading to activation of cGMP-dependent protein kinase to modulate physiological mechanisms such as vasodilation, fibrosis, and inflammation (Buys et al, 2018). In animal studies, praliciguat treatment resulted in increased cGMP levels in many tissues (Tobin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%